Obtenção de vesículas de gás isoladas de microrganismos para atuarem como agentes de contraste de ultrassom - Garrute, Felipe Vianna (2020)
Ultrasound contrast agent (UCA), used to enhance the contrast in ultrasonography, consists of microbubbles filled with an inert gas and encapsulated with a protein- or lipidic-stabilize membrane. Recently, a technique to produce UCA from microorganisms, as Halobacterium salinarum NRC-1 (HALO-NRC1), was developed and it consists in lysing microorganism’s cells to obtain gas vesicle (GVs) after cultivation in laboratory. This Dissertation implemented a technique to produce GVs from Microcystis aeruginosa MC-22 (MYC-22), at the Ultrasound Laboratory (LUS), and inspected their properties of acting as ACUs, analyzed through ultrasonic images, and morphology, diameter and length. The GVs from HALO-NRC1, already existent in LUS, were also inspected. After cultivation of MYC-22 and HALO-NRC1 and their grow in specific conditions the buoyant cells with GVs were separated from the culture medium and submitted to cells lysis with chemical treatment. Thereafter, the solution with lysed cells was centrifuged to isolate the GVs and each specie produced different GVs concentrations. Transmission electron microscopy inspection revealed the MYC22-GVs (n=15) with elliptical morphology and a medium diameter 0.171 (SD = 0,032) μm and length 0.201 (SD = 0,031) μm. Meanwhile, the GVs from HALO-NRC1 (n=15) presented a spindle-cylindrical geometry and a medium diameter 0.241 (SD = 0,041) μm and length 0.376 (SD = 0,091) μm. B-mode ultrasound images of the solutions proved the GVs ability to generate an echo signal, thus confirming their performance as ACUs.